Network compatibility and incumbent pricing regimes - Noriaki Matsushima; Mark J. Tremblay (Osaka University, Institute of Social and Economic Research (ISER), 2024)
The phenomenon where a network's value escalates with each additional user, known as a direct network effect, exists across industries that may differ in terms of interoperability or compatibility. For instance, while email and telephone services benefit from seamless cross-network communication, social media platforms typically do not, operating in silos (with some exceptions). Recent legislative initiatives, such as the Digital Market Act, spotlight the challenges and opportunities of enhancing network interoperability. This has led to a reevaluation of interoperability's impact on consumer benefits and API-driven business models, and industry experts and companies are now exploring increased interoperability. Our study introduces a model assessing the compatibility decision, whether by individual firms or unilaterally for the entire industry, and considers how this decision is linked to price regime decisions (personalized or uniform) in markets with direct network effects. We show that the two decisions are often linked, that parties often differ in their preferences across them, and that unilateral compatibility decisions can be used to deter entry and reduce competition.
Keywords: 330; Interoperability; Direct Network Effects; Personalized Pricing; Uniform Pricing